Dynamic leadership models for global business enhancing digitally connected environments - Smith, Peter A. C., 1933- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2013)
"This book describes various models on how to become an outstanding leader in today's rapidly growing global business environment, providing positive instruction that illuminates a practical path to becoming a successful leader in large and competitive markets"--Provided by publisher.